The Effect Of Creativity Toward Students’ Achievement in Writing Ability - Ning Setio Wati (Jurnal Pedagogy, 2018)
Writing is an activity to write and reformulate ideas to create meaning on a paper. In teaching writing, there are many influences, such as creativity. Creativity is an ability to create new product that can be useful and effective in original of thinking. This research is aimed at finding out whether creativity has significance influences toward writing achievement. The research was conducted at IAIN Metro in the academic year of 2012/2013. The population of this research was the third semester students of English Department of IAIN Metro. The result of this research is the students who have creativity could give significant effects on the students' writing ability and the creativity that was given by the lecturer was effective.